Analysis of the Effect of Human Resource Development and Career Development on Talent Management Formation (Survey At PT Bank Danamon, Tbk In Bandung Area) - Kosasih Kosasih (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of human resource development and career development on the formation of talent management at PT. Bank Danamon Tbk, In the Bandung Area. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study that human resource development has a significant effect on the formation of talent management by 37.9%, hypothesis testing is obtained t count > t table or (7.569 > 1.986). Career development has a significant effect on the formation of talent management by 42.4%; hypothesis testing is obtained t count > t table or (8.326 > 1.986). Human resource development and career development simultaneously have a significant effect on the formation of talent management with the regression equation Y = 9.581 + 0.347X1 + 0.426X2. The influence contribution is 50.4%, hypothesis testing is obtained by F arithmetic > F table or (47.342 > 2,700).